2015
DOI: 10.1159/000381782
|View full text |Cite
|
Sign up to set email alerts
|

Techniques to Reduce the Placebo Effect in Glaucoma Clinical Trials

Abstract: Aim: To evaluate techniques used to reduce the placebo effect in prior well-controlled, single or double-masked placebo-controlled glaucoma trials. Methods: This study was a retrospective, non-patient-based, observational review of phase I-III trials with a placebo arm for glaucoma medicines available after 1977. Results: This study included 20 articles with 20 placebo control arms consisting of 458 patients evaluating 10 different glaucoma medications with 58 treatment arms. There was no statistical differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…A previous study on glaucoma patients reported that the regression towards the mean might influence the placebo effect [ 22 ]. The results of the present study are not consistent with the findings of a previous study, which showed that setting a separate day entry criterion of IOP did not effectively restrain the placebo effect [ 20 ]. However, because the previous study only used averages rather than pulling the data from each patient individually, the obtained results would be expected to differ from those of the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A previous study on glaucoma patients reported that the regression towards the mean might influence the placebo effect [ 22 ]. The results of the present study are not consistent with the findings of a previous study, which showed that setting a separate day entry criterion of IOP did not effectively restrain the placebo effect [ 20 ]. However, because the previous study only used averages rather than pulling the data from each patient individually, the obtained results would be expected to differ from those of the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, because the previous study only used averages rather than pulling the data from each patient individually, the obtained results would be expected to differ from those of the current study. In particular, the use of only summaries of published data, rather individual patient data [ 20 ], meant the association between the glaucoma patients’ individual characteristics and placebo effects could not be fully ascertained. In this regard, the strength of the present study was the inclusion of individual-level patient data from the clinical trials.…”
Section: Discussionmentioning
confidence: 99%